2020
DOI: 10.1029/2020je006519
|View full text |Cite
|
Sign up to set email alerts
|

Macroporosity and Grain Density of Rubble Pile Asteroid (162173) Ryugu

Abstract: Upon arrival of the Hayabusa2 spacecraft, the C-complex asteroid (162173) Ryugu was found to be a spinning top-shaped rubble pile (Watanabe et al., 2019) with Cb-type spectrum and very low albedo around 0.045, consistent with thermally metamorphosed CM/CI meteorites (Sugita et al., 2019). Observations further show that a weak 2.7-μm absorption is present, suggesting a small amount of hydrated minerals exist on the surface (Kitazato et al., 2019). Furthermore, the surface was found to be dominated by blocks and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 71 publications
2
21
0
Order By: Relevance
“…They conclude that the low thermal inertia is intrinsic to the boulder and is indicative of high porosity (and low density and strength). Grott et al (2020) also confirmed this inference of high boulder porosity, and low bulk macroporosity of Ryugu, through extrapolation of the size-frequency distributions for boulders observed on Ryugu's surface. Using high-resolution optical and thermal imaging of Ryugu from the Hayabusa2 spacecraft, Sakatani et al (2021) found several boulders that are darker than the average surface and lower in thermal inertia than the MASCOT boulder.…”
supporting
confidence: 66%
“…They conclude that the low thermal inertia is intrinsic to the boulder and is indicative of high porosity (and low density and strength). Grott et al (2020) also confirmed this inference of high boulder porosity, and low bulk macroporosity of Ryugu, through extrapolation of the size-frequency distributions for boulders observed on Ryugu's surface. Using high-resolution optical and thermal imaging of Ryugu from the Hayabusa2 spacecraft, Sakatani et al (2021) found several boulders that are darker than the average surface and lower in thermal inertia than the MASCOT boulder.…”
supporting
confidence: 66%
“…It remains to be seen whether particle saturation (assuming it is present) is unique to rubble-pile asteroids such as Bennu and Ryugu, or if there is simply a lack of observations from analog features (e.g., lag deposits) on larger planetary bodies. Recently, Grott et al [68] proposed that Ryugu's PSFD is better described by a Weibull distribution of the form N(D) = N T exp(−3(D/λ) β /β),…”
Section: Comparison To Ryugumentioning
confidence: 99%
“…2001). A similar analysis of rubble-pile asteroid Ryugu is presented by Grott et al (2020), who report a macro-porosity of (16 ± 3)% using the surface SFD from Michikami et al (2019). Their analysis relies on detailed modeling of the rubble characteristics, including effects from rubble size and shape distribution.…”
Section: Discussionmentioning
confidence: 75%